2004
DOI: 10.1002/gcc.20150
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide variants within the IQGAP1 gene in diffuse‐type gastric cancers

Abstract: IQGAP1 is recognized as a negative regulator of cell-cell adhesion at adherens junctions in several cell types, including gastric mucosal cells. The histopathologic appearance of diffuse gastric carcinoma is defined by non- or poorly cohesive tumor cells, indicating abnormal intercellular adhesion. Hence, we screened 38 gastric cancers for activating point mutations in IQGAP1. In 2 of the 33 diffuse gastric cancers, there was a missense nucleotide change predicted to alter the amino acid sequence in the GAP-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The source of the interaction between APC and IQGAP1 20 relates to cell migration. The two genes have also been associated previously with colorectal cancer 21,25 and directly to CD. 30 More precisely, germline mutations (in which gene APC) cause familial adenomatous polyposis (FAP), which is an autosomal dominant inherited disease characterized by the presence of adenomatous polyps in the colon and rectum, with the inevitable development of colorectal cancer.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The source of the interaction between APC and IQGAP1 20 relates to cell migration. The two genes have also been associated previously with colorectal cancer 21,25 and directly to CD. 30 More precisely, germline mutations (in which gene APC) cause familial adenomatous polyposis (FAP), which is an autosomal dominant inherited disease characterized by the presence of adenomatous polyps in the colon and rectum, with the inevitable development of colorectal cancer.…”
Section: Discussionmentioning
confidence: 68%
“…Its role in carcinogenesis has already been reported, 23 and it has been mentioned that IQGPA1 might be involved in gastric and colorectal cancers. 24,25 Figure 1 Overall analysis of the WTCCC data. Quantile -quantile plots of the test statistic observed in the seven studied diseases.…”
Section: Resultsmentioning
confidence: 99%
“…A M1231I IQGAP1 mutation was occasionally seen in certain human cancers (29). We examined this mutation in 70 thyroid tumor samples but found only one case (1.4%) to harbor this mutation.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that 2 of 33 diffuse type gastric cancer samples contained a mutation in codon 1231 of the GRD (43). This mutation converts the native methionine to an isoleucine.…”
Section: Resultsmentioning
confidence: 99%